2021
DOI: 10.3390/foods10030591
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Mode of Action of Celastrol, a Nortriterpen Quinone Isolated from Natural Sources

Abstract: Species of the Celastraceae family are traditionally consumed in different world regions for their stimulating properties. Celastrol, a triterpene methylene quinone isolated from plants of celastraceas, specifically activates satiety centers in the brain that play an important role in controlling body weight. In this work, the antimicrobial activity and mechanism of action of celastrol and a natural derivative, pristimerin, were investigated in Bacillus subtilis. Celastrol showed a higher antimicrobial activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 60 publications
3
12
0
Order By: Relevance
“…The antibacterial activity of celastrol was tested against CRK isolates with no inhibitory activity observed for concentrations up to 1024 µg ml −1 . This is consistent with previous study reported that celastrol showed low MIC against Gram-positive bacteria and no growth inhibitory activity against Gram-negative bacteria in the used concentration [ 12 ]. Our study presumed that celastrol possibly acts by the same mechanism on both Gram-positive and Gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The antibacterial activity of celastrol was tested against CRK isolates with no inhibitory activity observed for concentrations up to 1024 µg ml −1 . This is consistent with previous study reported that celastrol showed low MIC against Gram-positive bacteria and no growth inhibitory activity against Gram-negative bacteria in the used concentration [ 12 ]. Our study presumed that celastrol possibly acts by the same mechanism on both Gram-positive and Gram-negative bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…Celastrol has been recently exploited to treat obesity and type 2 diabetes mellitus [ 11 ]. In addition, celastrol has been found to exhibit a growth inhibitory activity against Gram-positive bacteria [ 12 ]. Furthermore, celastrol was found to reduce staphyloxanthin biosynthesis and biofilm formation in Staphylococcus aureus [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, celastrol treatment makes B. subtilis cells elongated and spindle-shaped. Using transmission electron microscopy, celastrol has been shown to damage cell membranes to a certain extent ( 74 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, celastrol treatment makes B. subtilis cells elongated and spindle-shaped. Using transmission electron microscopy, celastrol has been shown to damage cell membranes to a certain extent 80 . Altogether, although the bactericidal effects of the identified PMF inhibitors (e.g., nordihydroguaiaretic acid, gossypol, trifluoperazine, amitriptyline, and alexidine) have already been highlighted in the literature, their effects on persister cells, to the best of our knowledge, have not been well characterized.…”
Section: Discussionmentioning
confidence: 99%